Educating software engineers an industry viewpoint. - Reifer, Donald J.
When Peter Henderson asked me to comment on the software engineering curricula proposed by the IEEE and ACM Joint Task Force1, I was thrilled. I thought the idea of academics asking for industry input to be strikingly original. I then dug into the proposed curriculum to determine if it would help prepare those from academia entering the software engineering workforce with the skills, knowledge and abilities they need to build quality software products on-time and within budget. Software engineers in most industrial organizations are problem solvers who perform difficult tasks like interfacing with users, developing requirements, specifying interfaces, performing design tradeoffs, developing algorithms and testing and evaluating products. They must be able to communicate with others from associated engineering disciplines, like communications and systems engineering, and work as members of interdisciplinary teams.
Keywords: Computing milieux; Computers and education; Computer and information science education; Curriculum; Software; Software engineering; Computer science education